Henry Morgan seventeenth-century buccaneer - Weintraub, Aileen (New York : Rosen, 2002)
Traces the life of Henry Morgan, famous buccaneer who never thought of himself as a pirate.
Includes index.
AR
K-3.
3.
Accelerated Reader
Keywords: Morgan, Henry, -- 1635?-1688.; Pirates -- Biography; Caribbean Region -- Description